2007
DOI: 10.1101/gad.1497307
|View full text |Cite
|
Sign up to set email alerts
|

Shugoshin enables tension-generating attachment of kinetochores by loading Aurora to centromeres

Abstract: Fission yeast shugoshin Sgo1 is meiosis specific and cooperates with protein phosphatase 2A to protect centromeric cohesin at meiosis I. The other shugoshin-like protein Sgo2, which requires the heterochromatin protein Swi6/HP1 for full viability, plays a crucial role for proper chromosome segregation at both mitosis and meiosis; however, the underlying mechanisms are totally elusive. We here demonstrate that, unlike Sgo1, Sgo2 is dispensable for centromeric protection of cohesin. Instead, Sgo2 interacts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
252
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(280 citation statements)
references
References 55 publications
18
252
2
5
Order By: Relevance
“…The role of Sgo in the regulation of mitotic cohesion has been addressed in a number of recent studies, mainly in yeast and human cells McGuinness et al 2005;Vaur et al 2005;Kitajima et al 2006;Tang et al 2006;Kawashima et al 2007;Vanoosthuyse et al 2007;Lee et al 2008). However, this is the first time that the Xenopus egg cell free system, in which vertebrate cohesin was initially characterized, is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of Sgo in the regulation of mitotic cohesion has been addressed in a number of recent studies, mainly in yeast and human cells McGuinness et al 2005;Vaur et al 2005;Kitajima et al 2006;Tang et al 2006;Kawashima et al 2007;Vanoosthuyse et al 2007;Lee et al 2008). However, this is the first time that the Xenopus egg cell free system, in which vertebrate cohesin was initially characterized, is used.…”
Section: Discussionmentioning
confidence: 99%
“…c One-μl aliquots of each depleted extract were analyzed by immunoblotting and compared with a mock-depleted extract to estimate the extent of depletion. Bars, 10 μm components (Kawashima et al 2007;Vanoosthuyse et al 2007;Yu and Koshland 2007). The interdependence of Aurora B and Sgo localization at centromeres remains to be investigated in detail, but it is likely to underlie the role of both proteins as sensors of tension across the sister kinetochores (Goulding and Earnshaw 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Studies in fission yeast have also shown that Sgo2 interacts with and promotes the centromeric localization of INCENP/ Survivin. 69,70 It is less clear if the centromeric localization of Aurora kinase is also regulated by Sgo2, although it could do so indirectly via INCENP. Finally, in mammalian cells Sgo2 also seems to promote MCAK localization at the centromere and cells depleted of Sgo2 exhibit erroneous kinetochore-microtubule attachments and high rates of chromosome mis-segregation in anaphase.…”
Section: How Does Aurora B Detect Kinetochore-microtubule Mis-attachmmentioning
confidence: 99%
“…199 In Schizosaccharomyces pombe, Shugoshin2 interacts with Bir1/Survivin and promotes Aurora kinase complex localization to the pericentromeric region, to correct erroneous attachment of kinetochores, thereby enabling tension-generating attachment. 200 Thus, Shugoshin2 might also be a component of the tension-sensing machinery. 201 The understanding of Shugoshin function gives new insights on spindle checkpoint and chromosome separation.…”
Section: Specific Space-time Protection Of Centromeric Cohesins Durinmentioning
confidence: 99%